TERRITÓRIO DO SAMBA E IDENTIDADES CULTURAIS: PROCESSOS DAS REDES EDUCATIVAS NOS MORROS DA PIEDADE E FONTE GRANDE - Silva Júnior, Jocelino da Conceição (2021)
The present research approaches the hills of Piedade and Fonte Grande, in the center of Vitória, as samba territory, because this territory is the cradle of samba in Espírito Santo, where the first samba school emerged in 1955. The general objective aspect of this work is to understand different educational processes among the educational networks present in the Piedade and Fonte Grande hills, with regard to the constitutions of cultural identities in the territory of samba. As specific objectives, we list the historicization of the contribution of the territory of the mountains and the grandeur of the capixaba culture; identify the educational processes in/of the territory and as educational networks that enhance sociability and social transformation; and, to present, as an educational product resulting from the professional master's degree, a proposal for pedagogical training with the people involved in the educational networks of the samba territory. The methodology of this research is qualitative in nature with data from readings, photographs, maps, conversations, walks with field diaries and a focus group, with representatives of the educational networks of the territory. To do so, in the critical approach research methodology, according to Lavoie, Marquis and Laurin (1996) and in the theoretical-methodological aspects of research with the educational networks of the second and everyday, Nilda Alves (2019). We dialogue with studies on racism, school and education with Nilma Lino Gomes (2017) and with Almeida (2018) about the notion of black population and racism. The studies of Milton Santos (2011) in the auxiliaries with the notion of territory; and, the formation of the samba territory, with the studies of Oliveira (2011) and Ciccarone (2009). To think about education, we are guided by the notion of education as a practice of freedom and social transformation with Paulo Freire (1987). The data and results of this research reveal different knowledge of the residents, as well as the educational networks and processes of the samba territory.